Aspects of the Well-being of University Instructors Related to Online Education During and After the Pandemic – Case Study of a Hungarian University - András Buda; Emese Beáta Berei (Central European Journal of Educational Research)
In the past decade, quite a few articles have been published about the advantages and disadvantages of working from home online, and by studying the experiences that they present, it would be possible to much more thoroughly plan the rather complex, multi-faceted process of digital transition. However, the coronavirus epidemic that broke out in early 2020 did not allow for thoughtful preparation. The new work schedule resulted in profound changes to the work of university lecturers, thus, it obviously also had a significant impact on their well-being. In this study, we examine the state of the well-being of the instructors at one of the biggest universities in Hungary, the University of Debrecen. The period in question is at the introduction of emergency remote teaching and at the end of the pandemic period. Using quantitative and qualitative methods, we collected data and information at different times. Based on this, we revealed what resources the instructors relied on, how they were able to meet the challenges of education online.